DIGITAL PLATFORMS AND THEIR IMPACT ON GLOBAL MARKETS (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
In today's world, digital platforms have become an integral part of global economic processes, transforming traditional industries and creating new opportunities for businesses and consumers. This article analyses the impact of digital platforms on the global economy, examining their key types: commercial, social, financial, and technological platforms. The author emphasizes how digital platforms help reduce transaction costs, enhance competition, and create new market models, while also increasing the accessibility of services and products for different segments of the population.At the same time, the paper highlights the challenges associated with market monopolization by large platforms, cybersecurity threats, and issues regarding user data privacy. Special attention is given to the social and geopolitical aspects of platform influence, including changes in consumer behaviour and the intensification of competition between countries for control over technological resources.The article discusses the future prospects for digital platforms, including their integration with artificial intelligence, blockchain, and other advanced technologies. Regulatory measures and strategies for minimizing risks to the global economy are also explored. The author concludes that balancing the potential of digital platforms with addressing the challenges related to their widespread adoption is crucial.This work will be useful for researchers, specialists in economics and digital technologies, as well as a broad audience interested in the current trends in global market development.